Who decides? ‘Shared’ decision-making in the surgical treatment of early breast cancer in northern Sri Lanka - Chrishanthi, R.; Kumar, R.; Gopikha, S.; Dhivya, T.; Suman, M.; Sutharshan, V. (Jaffna Medical Association, 2024)
Introduction: Shared decision-making (SDM) refers to clinicians and patients collaboratively making decisions based on the best available evidence. SDM encourages patients to consider the options, their benefits and risks, and communicate their preferences to clinicians. SDM has been associated with better adherence to treatment, less unwarranted intervention, and greater satisfaction with cancer care. This study explores the role of SDM in the treatment choices of women with early breast cancer who underwent mastectomy while eligible for breast-conserving surgery (BCS) in northern Sri Lanka. Method: An exploratory descriptive qualitative study was carried out among 15 women who underwent mastectomy for early breast cancer. Patients referred to Tellippalai Trail Cancer Hospital for adjuvant therapy after mastectomy and matched the study criteria were recruited. Data were collected through in-depth semi-structured interviews, which were transcribed in Tamil, translated into English, coded using QDA Miner Lite software, and analysed thematically. Results: Of 15 participants, three were not informed of BCS as a treatment option before mastectomy. The remainder were aware, but six women did not know they were eligible for BCS, while another five were steered towards mastectomy by treating teams who conveyed possibilities of spread or recurrence following BCS. Only one participant had selected mastectomy despite the surgeon recommending BCS. All but two women ‘shared’ decision-making with their spouses, children, siblings and others, who viewed mastectomy as the safer option. Pre-surgical counselling was often too brief; the complications following mastectomy were conveyed, but the possibility of needing adjuvant therapy was frequently not communicated. Neither the survival rates nor risks/benefits of the two surgical options were discussed. Despite the information gaps, many believed they received sufficient information. Conclusions: Patient narratives suggest that SDM may not be widely practiced in the surgical treatment of breast cancer in northern Sri Lanka. High patient-to-staff ratios and the unavailability of supportive care teams pose significant barriers to practicing SDM in the local setting.
Keywords: Shared decision-making; Mastectomy; Breast-conserving surgery; Pre-surgical counselling; Supportive cancer care